Tecnologias; educação e seus sentidos: o movimento de um grupo de pesquisa sobre interdisciplinaridade - GEPI - Miranda, Raquel Gianolla (2008)
This research involves the analysis of the process of appropriation of the usage of virtual environments based on the Internet by the Interdisciplinarity research group GEPI, coordinated by Ivani Catarina Arantes Fazenda, P.H.D. It deals with the investigation of the movement which this group pursued to establish its communication, the socialization of materials and registers, the study and the dialogue with distant colleagues and the possibility of establishing a virtual reflective environment on the theme Interdisciplinarity. An analysis based on the principles of an interdisciplinary education. In order to do so, we searched for an insight into the theory which firstly, has taken us to rescue the meaning of words as education, long distance education, technology, studying and dialogue among others, showing in such a manner, an educational context which this Interdisciplinarity insight demands. We concluded that the exercise of appropriation of virtual environments in an interdisciplinary perspective navigates slowly but solidly in communicative terms. At the same time and paradoxically, the quick productive moments after the use of virtual Internet resources were remarkable. We could also observe that the amplitude that the word Education possesses makes it difficult for us to establish the limits between long distance education and traditional classroom teaching. Finally, we concluded that the Interdisciplinarity insight into this problem has led us not to dismiss our built conceptions acquired by experience in the name of virtual environments, but rather to aggregate the specific considerations of each educational virtual environment within the already built frame of experience